Influence Of Joint Television Viewing On Romantic Satisfaction And Family Commitment: A Study Of Spouses In Delta State Secretariat Complex Asaba - Nwabueze, Chinenye; Odishika, Emmanuel (Advances in Social Sciences Research Journal, 2018)
The subject of this research is the influence of joint television viewing on the romantic satisfaction and family commitment of spouses in Delta State Secretariat Complex, Asaba, Delta state. The study adopted the purposive sampling method also known as judgmental sampling. The instrument of data collection was the interview guide. One hundred and twenty six (126) spouses were purposively selected and studied in this work. All the respondents were individually subjected to an average of 30 minutes long in-depth interview conducted over a period of three (3) months. The cultivation theory and the uses and gratifications theory served as the guiding theories for the study. The major objective of the study was to assess the influence of joint television viewing of programmes on the romantic satisfaction and family commitment of spouses in the secretariat. The result showed a great correlation between joint television viewing of love related programmes and the romantic satisfaction as well as family commitment of spouses in the secretariat complex. However, this degree of correlation was absent in the case of joint television viewing of other programmes that are not love related. Therefore, the paper recommends, among others, that spouses should selectively expose themselves to love stories that teach selfless love and sacrifice rather than those with default story lines that tend to be acrimonious and divisive of couples.